2016
DOI: 10.1021/acs.jproteome.6b00366
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and Combinatorial Landscape of Histone Modifications during the Intraerythrocytic Developmental Cycle of the Malaria Parasite

Abstract: A major obstacle in understanding the complex biology of the malaria parasite remains to discover how gene transcription is controlled during its life cycle. Accumulating evidence indicates that the parasite’s epigenetic state plays a fundamental role in gene expression and virulence. Using a comprehensive and quantitative mass spectrometry approach, we determined the global and dynamic abundance of histones and their covalent post-transcriptional modifications throughout the intra-erythrocytic developmental c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(89 citation statements)
references
References 75 publications
(168 reference statements)
7
80
2
Order By: Relevance
“…[20][21][22] At least 500 individual histone PTMs on different amino acid positions were identified recently on P. falciparum histonep roteins in ap roteomic screen, and so far 106 PTMs were experimentally validated in the follow up studies. [23][24][25] The acetylation of histonet ails is primarily involved in the gene activation process, whereas methylation is involved in both gene activation ands uppression. The potential target lysineso fh istone proteins in P. falciparum that are subjected to acetylation and methylation have been identified (Table 1).…”
Section: Chromatin Modifiers Of P Falciparummentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22] At least 500 individual histone PTMs on different amino acid positions were identified recently on P. falciparum histonep roteins in ap roteomic screen, and so far 106 PTMs were experimentally validated in the follow up studies. [23][24][25] The acetylation of histonet ails is primarily involved in the gene activation process, whereas methylation is involved in both gene activation ands uppression. The potential target lysineso fh istone proteins in P. falciparum that are subjected to acetylation and methylation have been identified (Table 1).…”
Section: Chromatin Modifiers Of P Falciparummentioning
confidence: 99%
“…The histone core protein and N‐terminal tails are subjected to many modifications including methylation, acetylation, and phosphorylation . At least 500 individual histone PTMs on different amino acid positions were identified recently on P. falciparum histone proteins in a proteomic screen, and so far 106 PTMs were experimentally validated in the follow up studies . The acetylation of histone tails is primarily involved in the gene activation process, whereas methylation is involved in both gene activation and suppression.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, high-sensitivity mass spectrometry experiments have identified a total of 232 different histone PTMs during the P. falciparum intraerythrocytic stages, including acetylations, methylations, phosphorylations, ubiquitylations, and sumoylations [89]. Many of these histone PTMs had never been detected in Plasmodium or in other organisms, and their exact function remains to be determined.…”
Section: Histones and Nucleosome Landscape Of P Falciparummentioning
confidence: 99%
“…Additionally, changes in nucleosome occupancy during parasite development have also been confirmed by alternative approaches. Experiments, including western blots [112], mass spectrometry [89,100,113], MNase-Seq, FAIRE-Seq [102], and ChIP-seq [100], showed that histone levels are lower during the transcriptionally active trophozoite stage. This observation has prompted a model for gene regulation in the parasite genome where nucleosome eviction drives the massive transcriptional event observed at the trophozoite stage, which is followed by the schizont stage where the genome repacks in preparation for reinvasion.…”
Section: Histones and Nucleosome Landscape Of P Falciparummentioning
confidence: 99%
“…Also, new components of DNA damage systems with strong links to chromatin have also been studies using label free quantitative proteomics approaches [52, 53]. Lastly, label free quantitative proteomic methods have been used to study the dynamics of changes in histone modifications during the malaria parasite life cycle [54]. …”
Section: Revealing the Dynamics Of The Chromatin Proteomementioning
confidence: 99%